Anishinaabeg Elders’ Land-based Knowledge: Enacting Bagijigan for Health and Well-being - McGuire-Adams, Tricia (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Indigenous Elders carry knowledge systems that are embedded within their respective land-based systems of knowledge. When Indigenous Elders pass away, their knowledge systems, if not preserved and documented, also pass away, which has lasting impacts on the continuance of Indigenous knowledge and practices of health and well-being. As a result of the enduring presence of settler colonialism, Indigenous Elders pass away at far earlier ages in comparison to their non-Indigenous counterparts. This article shows the results of an Indigenous health and well-being research project led by an Anishinaabe community in partnership with an Anishinaabe researcher. Guided by Anishinaabeg Elders and a Community Advisory Board, this research project preserves and documents Elders' knowledge of the land for community use and asks, how does knowledge of the land inform our health and well-being practices? In this article, we argue that Elders' knowledge is integral for regenerating critical well-being practices. We demonstrate that placing Elders' knowledge at the forefront of our well-being is an actionable practice of ganandawisiwin or good health. Without such knowledge and practices, we risk missing an opportunity to learn about well-being practices from our most precious knowledge holders.